Bettina Mottura, Letizia Osti, and Giorgia Riboni (editors), Media and Politics. Discourses, Cultures, and Practices (Newcastle upon Tyne, Cambridge Scholars Publishing, 2017, 504 pp. ISBN 152-750-022-5) (Altre Modernità, 2020)
Bettina Mottura, Letizia Osti, and Giorgia Riboni (editors), Media and Politics. Discourses, Cultures, and Practices (Newcastle upon Tyne, Cambridge Scholars Publishing, 2017, 504 pp. ISBN 152-750-022-5)by Francesco Meledandri